Estrategias lúdicas y su incidencia en la enseñanza teórico - práctica de la asignatura de contabilidad con los estudiantes del primer año de bachillerato de la Unidad Educativa Enrique Ponce Luque del cantón Quevedo - Castillo Navas, Cindy Carolina (2017)
This work develops a revision and study of the appropriation of the playful term and its treatment as a didactic tool. The vision of the playful as a possibility of meaningful learning in an active and pleasant way with the firm belief in "that one does not go to school to learn, but to develop", as well as the vision of some students, to be taught as something tedious has generated the present investigation. The perspective of this work is to continue with the implementation of the playful as a didactic tool that develops integrally, generates joy and frees the individual in exchange for controlling it. In education the attitudes that are going to have to be practiced in life and to constitute the playful strategies in a pedagogical methodology of modern education are developed, the participative stimulation of the students towards the transformation of the immediate reality must be involved. He surrounds it, aware of it and directly related to the operative reality of accounting has developed this systematic research that provides an interesting variable in relation to the form of motivation in the student to learn accounting. The pedagogical orientation used is the constructivist educational model with a focus on meaningful learning, with the playful as a didactic strategy in the search for the formation of active subjects, capable of making decisions and making judgments of value, for which participation is desirable. Active teachers and students, who interact in the development of the class to build, create, facilitate, release, question, criticize and reflect on knowledge